2006
DOI: 10.1038/sj.cdd.4402019
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound CD95 ligand expressed on human antigen-presenting cells prevents alloantigen-specific T cell response without impairment of viral and third-party T cell immunity

Abstract: Genetically modified antigen-presenting cells (APC) represent an attractive strategy for in vitro immunomodulation. In the human system, APC expressing HLA-A1 and a membrane-bound form of CD95L (m-CD95L) were used for selective depletion of HLA-A1-specific T cells. In short-term assays, m-CD95L-expressing APC-induced apoptosis in activated T cells and the constitutive presence of m-CD95L and HLA-A1 expressing APC in long-term T cell cultures prevented the expansion of CD4 þ and CD8 þ HLA-A1-specifc T cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…Although Ag-independent T cell proliferation induced by anti-CD3/28 activation was inhibited by TRAIL to nearly 100%, inhibition of alloantigen-specific proliferation ranged between 25% and 60%. This might be due to the fact that Ag and TRAIL were not expressed on the same APC, because we could show earlier in the CD95/CD95L system that development of alloantigenspecific CTLs is prevented only if APCs coexpressed the alloantigen together with the death ligand CD95L (40). In addition, costimulation of TRAIL-R in T cells derived from patients with OS prevented CD3/28-induced T cell activation, proliferation, and cytokine secretion, suggesting that also proliferation of autoreactive T cells can be prevented by simultaneous activation of TCR, CD28, and TRAIL-R.…”
Section: Discussionmentioning
confidence: 98%
“…Although Ag-independent T cell proliferation induced by anti-CD3/28 activation was inhibited by TRAIL to nearly 100%, inhibition of alloantigen-specific proliferation ranged between 25% and 60%. This might be due to the fact that Ag and TRAIL were not expressed on the same APC, because we could show earlier in the CD95/CD95L system that development of alloantigenspecific CTLs is prevented only if APCs coexpressed the alloantigen together with the death ligand CD95L (40). In addition, costimulation of TRAIL-R in T cells derived from patients with OS prevented CD3/28-induced T cell activation, proliferation, and cytokine secretion, suggesting that also proliferation of autoreactive T cells can be prevented by simultaneous activation of TCR, CD28, and TRAIL-R.…”
Section: Discussionmentioning
confidence: 98%
“…All cell lines were grown in complete RPMI 1640 medium (Invitrogen) supplemented with 10% FCS (Lonza), 2 mM l-glutamine, and 1 mM sodium pyruvate at 37°C in a humidified atmosphere containing 7.5% CO 2 . Establishment of C1R.A1.puro and C1R.A1.CD95L cells were described previously (25). T cells were cultured in complete RPMI 1640 medium supplemented with 2% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…Although naive T cells are CD95 resistant, CD95 sensitivity develops 6-7 d after T cell activation (26). We have previously shown that expression of a noncleavable m-CD95L and HLA-A1 on APCs efficiently prevents development of HLA-A1-specific T cells in long-term T cell cultures in vitro (25). In this study, we analyze whether CD95L-expressing APCs in fact delete antigen-specific T cells or whether CD95 triggering instead prevents antigen-specific T cell priming in naive T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, the molecular mechanisms of this co-stimulatory function have never been elucidated. Recently, Strauss et al 12,18 reported that CD95 co-stimulation blocks the activation of naïve T cells by inhibiting TCR signaling. This is in line with our observations using high concentrations of CD95 agonists, and thus reflects the inhibitory branch of CD95 signaling.…”
Section: Modulation Of Primary T-cell Activation By Cd95mentioning
confidence: 99%